Use of robots in software testing - Osovschi, Irina; Maryška, Miloš; Sládek, Pavel; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
Robotization has gained significant popularity in recent years, serving as a mean to automate various processes, especially those involving repetitive tasks across different industries. This master's thesis focuses on exploring the application of robotization in software testing, specifically in the context of automating regression testing. The thesis comprises both theoretical and practical components. The theoretical part delves into the subjects of robotization, software testing, and Robotic Process Automation (RPA). The practical aspect involves a comparative analysis of test automation using RPA with UiPath and a professional testing tool represented by Provar. Salesforce, a widely utilized platform in diverse industries, is chosen as the testing subject for this comparative analysis. The findings of this study aim to provide insights into the suitability of robotization for developing automated tests, determining whether it is a viable option for this purpose or not. By examining the effectiveness of using robots in automating regression testing, this thesis contributes to the understanding of the potential benefits and limitations of robotization in software testing.
Vedoucí práce: Miloš Maryška
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: podniková informatika [obor dipl. práce]; diplomové práce; master's theses